(untitled) (American Journal of Islam and Society, 2014)
Nasir-i Khusraw (d. 469/1077), who was appointed by the Fatimid imam al- Mustansir bi’llah (d. 487/1094) as the ḥujjat and chief dā‘ī for the region of Khurasan, lived the later period of his life exiled in Badakhshan due to religious persecution. This treatise, a virtual summa of eleventh-century Ismaili philosophical theology put forth in a question-and-answer format, deals with almost all of the scientific and philosophical issues that occupied the minds of the Isma‘ili mission of his time. The context is a reply to the amīr of Badakhshan, Abu al-Ma‘ali ‘Ali ibn al-Asad (reign 462/1069), who had requested Nasir to explain Abu al-Haytham Ahmad ibn al-Hasan al-Jurjani’s (d. 10th century) philosophical qaṣīdah. The text itself, originally edited by Henry Corbin and Mohammed Mu‘in in 1953, offers an alternative reading to Latimah Parvin Peerwani’s clear but partial English translation, which was recently published in the second volume of An Anthology of Philosophy of Persia. Ibrahim al-Dasuqi Shata had translated the 1953 edition into Arabic in 1974, and Isabelle de Gastines’ French translation was made available in 1990. Although the majority of the text is written in prose and not poetry, it would still be pretentious in this short review to focus too critically on possible alternative readings. Any reader with competence in the original language and a concern for specific passages now has several translations, along with the edited text, from which to make a critical comparison. The fact remains that Ormsby has rendered a fluid and accurate translation that maintains the simplicity required to enable a broader audience to follow the complexity of Nasir’s ideas. An additional aid is also found in the copious footnotes, introductory essay, index, and bibliography, all of which not only explain the many obscure points in Nasir’s treatise, but also suggest many areas for future research. There is one question regarding the Persian text that does need additional clarification: Ismail K. Poonawala pointed out in his review of Faquir M. Hunzai’s edition and translation of Nasir’s Gushāyish va Rahāyish (translated as Knowledge and Liberation: A Treatise on Philosophical Theology) that the ...